Pest control in groundnuts - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1997)
Groundnuts (Quote PANS2) Pest Control Series 1996 348pp price UKL20 00 ISBN 0 85954 391 9